Bovine Fetal Mesenchymal Stem Cells Obtained From Omental Adipose Tissue and Placenta Are More Resistant to Cryoprotectant Exposure Than Those From Bone Marrow - Oyarzo, Rudy; Valderrama, Ximena; Valenzuela, Francisca; Bahamonde, Javiera (Frontiers in Veterinary Science, 2021)
Recent studies have shown promise for the development of cellular therapies with mesenchymal stem cells (MSCs) in livestock species, specifically bovines, and cryopreservation is highly relevant for the advancement of these applications. The use of permeable and/or non-permeable cryoprotectant solutions is necessary to reduce cell damage during freezing and thawing, but these same compounds can also cause negative effects on MSCs and their therapeutic properties. Another important factor to consider is the tissue source of MSCs, since it is now known that MSCs from different tissues of the same individual do not behave the same way, so optimizing the type and concentration of cryoprotectants for each cell type is essential to achieve a large and healthy population of MSCs after cryopreservation. Furthermore, sources of MSCs that could provide great quantities, noninvasively and without ethical concerns, such as placental tissue, have great potential for the development of regenerative medicine in livestock species, and have not been thoroughly evaluated. The objective of this study was to compare the viability of bovine fetal MSCs extracted from bone marrow (BM), adipose tissue (AT), and placenta (PT), following their exposure (15 and 30 minutes) to several solutions of permeable (dimethyl sulfoxide and ethylene glycol) and non-permeable (trehalose) cryoprotectants. Viability assays were performed with Trypan Blue to assess post-exposure plasma membrane integrity. The apoptotic potential was estimated analyzing the mRNA abundance of BAX and BCL-2 genes using quantitative rt-PCR. Based on the results of the study, BM-MSC exhibited significantly lower viability compared to AT-MSC and PT-MSC, at both 15 and 30 minutes of exposure to cryoprotectant solutions. Nevertheless, viability did not differ among treatments for any of the cell types or timepoints studied. BCL-2 expression was higher in BM-MSC compared to AT-MSC, however, BAX/BCL-2 ratio did not differ. In conclusion, AT-MSC and PT-MSC were more resistant that BM-MSC, which showed higher sensitivity to experimental conditions, regardless of the exposure times and cryoprotectant solutions used in the study.